2019
DOI: 10.17559/tv-20181015174733
|View full text |Cite
|
Sign up to set email alerts
|

Post-socialist Development and Rehabilitation of Large Housing Estates in Central and Eastern Europe: A Review

Abstract: In the socialist times, large housing estates in the Central and East European (CEE) cities were praised for effectively resolving the housing crisis, providing good and homogenous housing conditions at reasonable costs and enabling rapid urbanization. Following the collapse of communism, they have met with various consequences of low-cost construction based on prefabrication, lack of repair and upgrading investments and neglected or deferred maintenance, and the Western experience drew attention to the socioe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…As in the case of other post-socialist cities, such as Ostrava [79] or Novi Sad [45], the present study highlights the importance of small entrepreneurs and spontaneous initiatives in asserting the potential of creative activities to capitalize on the potential of former industrial spaces. A common element seems to be related to the inertia and outdated mentality of the authorities, for which only large-scale projects matter and their inability to perceive the multiple beneficial valences of creative activities in this field.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…As in the case of other post-socialist cities, such as Ostrava [79] or Novi Sad [45], the present study highlights the importance of small entrepreneurs and spontaneous initiatives in asserting the potential of creative activities to capitalize on the potential of former industrial spaces. A common element seems to be related to the inertia and outdated mentality of the authorities, for which only large-scale projects matter and their inability to perceive the multiple beneficial valences of creative activities in this field.…”
Section: Discussionsupporting
confidence: 59%
“…In Poznań, for example, one of the major innovative projects launched after 1990 was the rehabilitation of an industrial ensemble, the former brewery, and its transformation into a cluster of artists, young entrepreneurs, architects, and designers [43]. The same is true of New Belgrade, today one of the main areas of concentration of creative activities in Belgrade [44], and of the city of Novi Sad, where the post-industrial transformation of the Kineska neighborhood on the banks of the Danube has been achieved by means of a spontaneous and informal culture-based movement [45].…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…The shift in the political system was, logically, accompanied by the introduction of new policies in all spheres of government, including housing. As was the case in many other former socialist countries [38], the shift to a market economy system was readily accepted by the citizens who, at the time, entertained high expectations of future prosperity. But the euphoria did not last long.…”
Section: Post-socialist Mass Housing In Sloveniamentioning
confidence: 93%
“…And in order to realize the egalitarian doctrine, dwellings in large housing estates were allocated to all employees, i.e., functionaries of the Communist Party, middle class public employees (including university professors and medical doctors) and industrial workers, regardless of social status. Nedučin et al [38] (p. 1854) have suggested that "as a result, the socio-economic composition of large housing estates in the CEE cities presented a spectrum of various statuses and professions, making social heterogeneity their most distinguishing characteristic. "…”
Section: Political Ideologymentioning
confidence: 99%
See 1 more Smart Citation